The Influence of Promotion, Price, and Product on Online Purchasing Decisions - Mispandi, Mispandi; Fahrurrozi, Muh; SOka, Gina Mayang; Hakim, Muhammad Riswandi; Amelia, Shella Rizqi (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
This study aims to determine whether promotion, price and product have a significant effect on online purchasing decisions. The method used is a quantitative method. The population used in this study was 100 people who had purchased products online and the sampling technique used purposive random sampling. Data analysis techniques in this study were classical assumption tests, multiple linear regression, and hypothesis tests. The results of the research that have been carried out can be concluded that partially the promotion value (t count> t table 3.679> 1.985), price (t count> t table (3.679> 1.985), product (t count> t table 2.547> 1.9845) have a significant effect on online purchasing decisions while simultaneously promotion, price, product (F count> F table 37.677> 2.31) have a significant effect on online purchasing decisions.